Validation of Genderism and Transphobia Scale Indonesian Version: Short Version, Factor Structure, and Reliability - Sin, Gabrielle Sinata; Natalya, Lina; Jun, Isabel Chua Jia; Siaputra, Ide Bagus (Faculty of Psychology, Universitas Gadjah Mada, 2025)
This study aimed to develop a short version of the Genderism and Transphobia Scale (GTS) that is culturally appropriate for the Indonesian context. The GTS is a measuring tool developed by Hill and Willoughby in 2005 to measure transphobia, which is operationalized by the thoughts, feelings, and behavior that someone has toward transgender and gender-diverse people. While the GTS has been validated across various cultural contexts, results have varied. No validation study has been conducted in Indonesia to date. This research consisted of two quantitative studies using a non-random survey design: Study I involved 265 secondary data sources, and Study II involved 109 primary data sources. In Study I, the Indonesian short version of the GTS (GTS-SV) was developed using Exploratory Factor Analysis (EFA), Cronbach's alpha reliability testing, and inter-item correlation analysis. Study II evaluated the internal structure of the GTS-SV using the same analytical methods. Findings from both studies supported the validity and reliability of the Indonesian version of the GTS-SV. This scale provides a psychometrically sound instrument for assessing transphobia in Indonesia and may support future research and interventions aimed at fostering greater social acceptance of gender-diverse populations.